Pomolic acid induces ferroptosis-mediated cell death in non-small cell lung cancer - Ji, Wenbin; Zhang, Yanbin; Ji, Wenhao; Zhang, Hui; Qin, Biao; Xing, Xiao-Liang; Zhang, Zaiqi (Frontiers in Pharmacology, 2025)
IntroductionPomolic acid (PA), a bioactive compound derived from Potentilla freyniana Bornm., is used palliatively for non-small cell lung cancer (NSCLC) in China’s Dongzu region, with some reports of clinical efficacy. However, the specific underlying molecular mechanisms remain unclear. This study aimed to identify the core targets of PA and explore its function and potential mechanisms in NSCLC.MethodsNetwork pharmacological analysis was utilized to identify the core targets of PA. In vitro functional studies were performed using NSCLC cells to investigate PA’s effects on cell death and proliferation. Assays were conducted to measure hallmarks of ferroptosis, including glutathione (GSH) depletion, iron (Fe2+)-dependent lipid peroxidation, and elevated reactive oxygen species (ROS) levels. Protein expression levels of key anti-ferroptotic factors (SLC40A1, SLC7A11, GPX4) and pro-ferroptotic proteins (ACSL4, HO-1) were assessed. Quantitative PCR (qPCR) was used to determine mRNA expression levels of genes negatively regulating ferroptosis (GPX4, SLC7A11, NRF2).ResultsPA effectively induced cell death and inhibited proliferation in NSCLC cells. Characteristic hallmarks of ferroptosis were observed, including GSH depletion, Fe2+-dependent lipid peroxidation, and increased ROS levels. Protein expression levels of SLC40A1, SLC7A11, and GPX4 were significantly downregulated, while ACSL4 and HO-1 were markedly upregulated. mRNA expression levels of GPX4, SLC7A11, and NRF2 were also significantly reduced.DiscussionThese findings suggest that PA exerts its anticancer effects primarily through ferroptosis induction. The observed modulation of key ferroptosis-related proteins and genes supports this mechanism. Therefore, PA may serve as a promising therapeutic agent for NSCLC treatment.